Sexual problems of women aged 60+ with diagnosed obesity - Pawełko, Agnieszka; Ciechacka, Maria; Bąk, Ewelina (Journal of Education, Health and Sport, 2025)
Introduction Sexuality is a complex issue, but every person has the right to express it. Seniors are individuals with significant life experience. They are often curious people with much to say to younger generations. Let us allow them to function fully in society, respecting all spheres of life, allowing them to express their sexuality and diversity. Materials and Methods The research was conducted among 102 women, of which 35 were obese and 67 were not. This study employed the diagnostic survey method. The research was conducted using the SQOL-F questionnaire. Results: No negative impact of obesity was found across all domains of SQOL-F and its overall score. Conclusions: Among patients with obesity, there is no statistically significant negative impact of this condition on sexual aspects. Obese patients require greater focus on educational actions aimed at maintaining good dietary control, as well as regular visits and adherence to therapeutic recommendations.